Anti H.pylori IgM in Symptomatic and Asymptomatic Population - Sumona, Asma Azad; Hossain, MA; Musa, AK; Shamsuzzaman, AK; Mahmud, MC; Khan, MS; Ahmed, S; Begum, Z; Zahan, NA; Ahmed, MU; Debnath, CR; Anne, RA (Mymensingh Medical Journal, 2009)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> Mymensingh Med J. 2009 Jan;18(1):18-20. The abstract of this article is available on the PubMed website